The Effect of Managerial Ownership, Audit Committee, Profitability and Tax Avoidance on The Value of Manufacturing Companies for The Period 2018 - 2022 - Kesya Lusiana Putri; Riris Rotua Sitorus (Jurnal Syntax Transformation, 2024)
This research was conducted to determine the influence of managerial ownership, audit committee, profitability and tax avoidance on company value in manufacturing companies in the consumer goods sector for the 2018-2022 period. This research uses a purposive sampling model and the population in this research is manufacturing companies in the consumer goods sector, totaling 16 companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period that meet the criteria. The data analysis model used is panel data regression analysis. The research results in this study show that simultaneously the variables Managerial Ownership, Audit Committee, Profitability and Tax Avoidance have no influence on Company Value. However, partially the variables Managerial Ownership, Audit Committee, and Tax Avoidance do not have a significant influence on Company Value. Meanwhile, Profitability (ROA) has a significant influence on Company Value.